Provision of payments for ecosystem services to reduce air pollution: Case of Tehran - Morteza Tahamipour Zarandi; Mina Moghise (Transportation Research Interdisciplinary Perspectives, 2025)
The negative impacts of air pollution and its environmental, economic and social damages to metropolises are among urban management challenges. One of the most economically effective tools for environmental management and pollution control is payments for ecosystem services (PES). In this study, we have proposed the framework and requirements of PES to reduce Tehran air pollution using one of the most practical methods for reducing emissions of gaseous pollutants i.e. replacing passive catalytic converters in light vehicles in Tehran. For this purpose, we have investigated the owners’ willingness to participate in PES, the cost of replacing the converters and Tehran residents’ willingness to pay to reduce air pollution. The study results showed that on average, 71.3 % of Tehran citizens in the study sample agreed to pay. The willingness to pay per person has been calculated at 912 thousand Rials per month. Also, a significant percentage of owners agree to participate voluntarily to replace catalytic converters. The data presented in this study provided the framework of PES to reduce Tehran air pollution through urban management institutions and government participation in financing under various scenarios.